Maternal circulating leptin, tumor necrosis factor-alpha, and interleukine-6 in association with gestational diabetes mellitus: a systematic review and meta-analysis - Elham Hosseini; Zeinab Mokhtari; Amin Salehi Abargouei; Gita D. Mishra; Reza Amani (Taylor & Francis Group, 2023)
Background: Over the last decade, an emerging role of novel cytokines in the pathogenesis of gestational diabetes mellitus (GDM) has been proposed. The present study was implemented to provide a more accurate estimate of the effect size of the association between leptin, tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) and the risk of GDM.Methods: Online databases were looked up to January 2023 using the search string: (leptin OR TNF-α OR IL-6) AND "gestational diabetes." Observational studies investigating the association of selected cytokines and GDM risk were included. Odds ratios and their 95% confidence intervals (CIs) were extracted and random-effects models were used to estimate the pooled effect.Results: Twenty-four studies were included in the meta-analysis. A significant association was found between higher circulating leptin and the risk of GDM and the pooled estimate was 1.16 (95%CI: 1.07, 1.27). Higher circulating levels of IL-6 and TNF-α were associated with increased risk of GDM, and the pooled estimates were 1.35 (95%CI: 1.05, 1.73) and 1.28 (95%CI: 1.01, 1.62), respectively.Conclusions: The studied cytokines could be implicated in the GDM pathogenesis and used as potential biomarkers for assessing the GDM risk. Additional longitudinal studies with large sample sizes are needed for a further evaluation of these findings.